?Aqui ? tudo uma rama de maxixe?: experi?ncias de trabalhadores rendeiros da Fazenda Engenho Sururu, Varzedo-BA (1970-2000) - Assis, Viviane Andrade de (2013)
This text has as object to present the experiences of renters workers of the Engenho Sururu farm, located at the city of Varzedo, Bahia?s Rec?ncavo. Interests the work relationships of this renters through the constitution of an oral agreement with Humberto Guedes de Ara?jo ? the farm owner that was donated in the eighteenth century through the grant of sesmarias. The rural lease was signed between those who owned the land and who would worked on it. The landowner guaranteed the access to the land and established the conditions to stay in the lease. And the renter had to obligation to pay the rent, which guaranteed the right to live with his family as only in the mud houses and to plant subsistence farming in the leasehold lands. The study of this process allowed to understand how this relationship, based on an oral contract, poor living conditions, working and too in the solidarity, constituted itself as a reinvention of the exploration and resistance in the country. In that farm, these relationships appear to have been undertaken since when it housed workers in slave conditions, possibly, the ancestors of many of the families that still living there. From the analysis of these experiences mediated by oral narratives, the aim of this work is to understand about the land rights of the families that rented the lands of the Engenho Sururu farm, who live and work there for some generations, constituting, therefore, the ties of kindred among the community members, which is an element that gives the group unit, that is, "rama de maxixe"